THE DEAFNESS, THE DEAF AND HIS DISCURSE - Neuma Chaveiro; Maria Alves Barbosa (Universidade Federal de Goias, 2004)
The knowledge of LIBRAS Brazilian Sign Language is determining to the process of structuringthe discursive formations and to the constitution of the deaf one. The present work aims to discuss the LIBRAS asan important tool of structuring the discursive of the deaf individual an as a facilitating factor in the description of hishealth problems. The data constitute two texts, one of them wrote by a deaf skilled in LIBRAS and the other wroteby a deaf who does not express himself in this kind of language. It was verified that the first texts author isconsistent, has mobility and moves easily through the discursive formations, but otherwise is the text belonging tothe other patient. It can be stated that the Brazilian sign language LIBRAS is a decisive tool in the working outof the deaf discursive formations and the comprehension of his discourse by the health area professionals providea larger understanding of the constitution of the deaf identity, a fundamental aspect for an improvement in theservices offered in the health area.